OPEN DATA USAGE AND DIGITAL LITERACY LEVEL OF PEOPLES IN TANGERANG REGENCY - Ahmad Khumaeni Zhakaria; Ray Septianis Kartika; Nurkholish Majid (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The era of digitalization requires an innovative and accountable government. Tangerang Regency has a variety of applications that are realized to accelerate services and good governance as a whole. One of them is through open government data, which is easily accessible by any party to achieve a goal, namely transparency and disclosure of information. The purpose of this study is to determine the level of digital literacy of the community and the extent of their use of the open data portal. This research uses a mixed method with quantitative analysis using a Likert scale. The population and sample of the study were the people of Tangerang district aged between 18 and 60 years old, domiciled in Tangerang, and had used the district's open data portal. The results of this study indicate that although most people in Tangerang district have relatively high digital literacy skills, they still do not fully utilize this tool in the context of using the open data portal. This is due to several factors such as lack of public awareness, socialization from the government, and features that are not fully optimized.